ARDUINO UNO R3 MICROCONTROLLER-BASED DESIBEL (dB) METER DEVELOPMENT ALERT(CASE STUDY SDN 04 TAPAKTUAN) - Pia Rahmadani; Rudi Arif Candra; Dina Miftahul Jannah; Arie Budiansyah; Dirja Nur Ilham (Global Advances in Science, Engineering & Technology (GASET), 2025)
Noise is an environmental problem that arises due to the rapid growth of communication, industrialization, transportation, space, musical instruments and population. The purpose of this research is to detect the frequency value of sound intensity that can cause deafness and sound frequency that is safe for human hearing. The sound intensity value detected by the sensor is displayed in Real Time through Lcd. This tool research uses three parts, namely control, input and output, where Arduino nano functions as a tool controller, sound sensor as an input that functions as a sound detector around, dfplayer and Lcd as an output that functions to display sensor readings in the form of numbers and emit sound. Sound sensor reading data uses 4 categories, namely 0-30 dB “very safe”, 30-60 “safe”, 60-90 “dangerous” and 90-100 “very dangerous”, and the sound will sound according to the value displayed on the sound sensor to Arduino to facilitate the monitoring process. After the whole tool is assembled the tool is tested in two different places, namely Taman Pala and SDN 9 Tapaktuan South Aceh. The results of testing the tool in the nutmeg garden show a sound frequency number of 53.26 dB in the “safe” category, while the test results at SDN 9 show a frequency number of 98.93 dB in the “Very dangerous” category when the room is noisy.